Camera roll of Thanksgiving Dinner - Nathaniel Benchley:::Creator::::::::::::
Contact sheet of 15 photos of John Steinbeck (and others) at Benchley's home for Thanksgiving dinner. These are reputedly the last photos taken of John Steinbeck. number 0 628 is contained on this sheet. Original in safe